2022
DOI: 10.1001/jamainternmed.2021.7372
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of SARS-CoV-2 Antibody Response 4 Weeks After Homologous vs Heterologous Third Vaccine Dose in Kidney Transplant Recipients

Abstract: IMPORTANCEFewer than 50% of kidney transplant recipients (KTRs) develop antibodies against the SARS-CoV-2 spike protein after 2 doses of an mRNA vaccine. Preliminary data suggest that a heterologous vaccination, combining mRNA and viral vector vaccines, may increase immunogenicity.OBJECTIVE To assess the effectiveness of a third dose of an mRNA vs a vector vaccine in KTRs who did not have antibodies against the SARS-CoV-2 spike protein after 2 doses of an mRNA vaccine. DESIGN, SETTING, AND PARTICIPANTSThis was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
124
3

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 113 publications
(147 citation statements)
references
References 36 publications
(62 reference statements)
11
124
3
Order By: Relevance
“…Indeed, recent data suggested that a third dose COVID-19 vaccine could increase the seropositivity rate from 40 to 68% in KTRs with no serious adverse events reported ( 43 ). Heterologous vaccination strategy with a third dose being a vector-based vaccine demonstrated comparable immunogenicity and safety to that of mRNA vaccine among KTRs who remained seronegative after 2 doses of mRNA vaccine ( 44 ). Furthermore, based on the experience of using intradermal route or adjuvants for HBV and influenza vaccines in immunocompromised hosts ( 45 ), it is also worthwhile to investigate whether these approaches may potentially enhance the immunogenicity and clinical efficacy of COVID-19 vaccines in KTRs.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, recent data suggested that a third dose COVID-19 vaccine could increase the seropositivity rate from 40 to 68% in KTRs with no serious adverse events reported ( 43 ). Heterologous vaccination strategy with a third dose being a vector-based vaccine demonstrated comparable immunogenicity and safety to that of mRNA vaccine among KTRs who remained seronegative after 2 doses of mRNA vaccine ( 44 ). Furthermore, based on the experience of using intradermal route or adjuvants for HBV and influenza vaccines in immunocompromised hosts ( 45 ), it is also worthwhile to investigate whether these approaches may potentially enhance the immunogenicity and clinical efficacy of COVID-19 vaccines in KTRs.…”
Section: Discussionmentioning
confidence: 99%
“…Details on randomization and treatment have been reported before. 3 In short: 200 patients without detectable SARS-CoV-2 specific antibodies following two doses of an mRNA vaccine were randomized to a 3 rd dose of the same mRNA vaccine (mRNA group) or a dose of the vector vaccine Ad26COVS1. Clinical endpoints (death, COVID-19) were recorded for all study participants throughout the observation period.…”
Section: Methodsmentioning
confidence: 99%
“…We recently conducted a randomized single-blinded controlled trial in 200 patients comparing a homologous vs heterologous vaccination strategy in KTR who did not develop SARS-CoV-2 spike protein-specific antibodies after two doses of an mRNA vaccine: Overall, 39% of patients developed antibodies at four weeks after the 3 rd dose, with no statistically significant difference between an additional dose of the same mRNA vaccine as used for the initial prime/boost vaccination (BNT162b2 or mRNA-1273, 35% response rate) or a vector vaccine (Ad26COVS1, 42% response rate). 3 Other recent reports, however, suggest a more pronounced induction of both, a SARS-CoV-2 specific CD4 T cell response and antibodies following heterologous vaccination that includes a vector-based vaccine in transplant recipients. 4 In line, heterologous 3 rd vaccination also increased overall T-cell response in patients treated with B-cell depleting therapy.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…The detected levels of neutralizing antibodies have been shown to be higher after administration of the BioNTech/Pfizer vaccine BNT162b2 than those after receiving the AstraZeneca vaccine ChAdOx1, although this could not be shown for T-cell responses [13]. These differences have led to the discussion regarding potential benefit from a heterologous vaccination strategy [13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%